Research on Method of Phantom Track Generation Based on Cooperative Control of UAVs in Uniform Linear Motion. (November 2019) - Ouyang, Zhiping; Xu, Chen; Feng, Jiqiang; Wang, Bo
Abstract: In order to effectively interfere with the networking radar, this paper establishes a reverse-pyramid model firstly based on the uniform linear motion of UAVs and the characteristic of phantom track. Furthermore, the multi-UAV cooperative track deception model is built to analyze the locations and motions of UAVs. Finally, we design a simulation experiment to obtain the motion parameters of each UAV and analyze the minimum number and speed of UAVs.